Factors Affecting the Level of Usage of Online Food Ordering Portal Among UTHM student - Ahmad Rusydi Abdul Rashid; RAMASAMY, CHANDRASHEKAR (Research in Management of Technology and Business, 2024)
An Online Ordering Portal provides a convenient way for customers to order and purchase food without having to leave the house. The core idea of this paper was to empirically evaluate the factors affecting the level of usage of online food ordering portal among UTHM students. The goal was to explore the factor in the emerging industry of online food ordering portal among UTHM students. This paper used a quantitative method through the collection and analysis of data from a total of 341 survey respondents. All of the respondent are students who stay in Kolej Kediaman Dalam Kampus in Universiti Tun Hussein Onn. Statistical Package for Social Science (SPSS) will use to analyse the data. Statistical analyses of all collected data were used to conclude the factors important to consumers in ordering food online through online food ordering portal.